"The impact of debulking surgery in patients with node-positive epithelial ovarian cancer: Analysis of prognostic factors related to overall survival and progression-free survival after an extended long-term follow-up period". (March 2016) - Pereira, Augusto; Pérez-Medina, Tirso; Magrina, Javier F.; Magtibay, Paul M.; Rodríguez-Tapia, Ana; Cuesta-Guardiola, Tatiana; Peregrin, Irene; Mendizabal, Elsa; Lizarraga, Santiago; Ortiz-Quintana, Luís
Abstract: Objective: to estimate the prognostic factors associated with survival and progression free survival (PFS) in patients with node-positive epithelial ovarian cancer (EOC) after an extended long-term follow-up period. Methods: Data was provided by the Tumor Registry of the Mayo Clinic, Scottsdale, Arizona on 116 node-positive EOC patients who underwent primary cytoreductive surgery observed over the period 1996–2014. Results: At censoring date, 21 patients were alive (18%), 95 dead (82%), 18 without evidence of disease (NED) (15 alive, 3 dead) and 76 with evidence of disease (ED) (2 alive, 74 dead). Twenty-nine ED patients (38.2%) experienced a recurrence within 2 years, 53 patients (69.7%) before 5 years. No recurrences were recorded after 10 years. The median follow-up in alive patients was 169.8 months (1.20–207.9 months), 34.9 months (0.30–196.2 months) in dead patients, 128.4 months for NED patients (72.8–202.5 months) and 34.6 months (0.1–106.9 months) in ED patients. Multivariate analysis showed an increased risk of dead in patients with age ≥60 years (HR: 3.20; p < 0.002), stage IVA/B (compared with stage IIIA1/2, HR: 4.31; p < 0.001 and stage IIIB/C, HR: 5.31; p < 0.010) and incomplete surgery (compared with complete surgery, HR: 3.10; 95% CI, 1.41–6.77; p < 0.003) and a decreased PFS in stage IVA/B (compared with stages IIIB/C; p = 0.003 and stage IIIA; p = 0.000) and residual volume after surgery >0.6 cm (compared with residual disease <0.5 cm; p < 0.023). Conclusions: prognostic factors for an extended long-term PFS are similar as those for survival, because after 17-year follow-up period, the majority of alive patients are NED patients. Highlights: In node-positive EOC, prognostic factors for extended long-term periods are unknown. PFS and survival factors are similar, because 79% of living patients had NED. Those factors are the extent of disease, and residual disease after surgery.